A Systematic Review of Gen-AI Applications in Education: Rewards, Challenges and Future Prospects - Everleen Nekesa Wanyonyi; Millicent Kathambi Murithi (Pan-African Journal of Education and Social Sciences)
Recent advancements in Artificial Intelligence (AI), particularly in Generative AI, have significantly impacted various domains. Innovation of models such as ChatGPT, Bard, DALL-E, Midjourney, and DeepMind has transformed academia. The widespread use of AI systems has sparked debates on how to effectively train future-relevant competencies while maintaining learning integrity. The ability of GenAI algorithms to generate specific feedback on tests, quizzes, and assessments as an instructional instrument to support student success has been a significant motivator. With current challenges of insufficient academic resources, a freeze on teacher hiring, and a shortage of practice space in developing countries, GenAI has become a handy tool to save the situation. Despite this boost, GenAI has faced major academic and ethical controversies. This study uses the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) methodology to conduct an exhaustive literature search highlighting GenAI’s applications, benefits, challenges, and future prospects in the education sector. Key findings highlight the efficacy of enhancing the theoretical basis of AI in education and offer a promising avenue for educators and AI engineers to conduct collaborative research.